Texto impreso "FÍSICA EXPERIMENTAL" y el aprendizaje de los estudiantes en el área de Ciencia Tecnología y Ambiente del 5to grado de Educación Secundaria en la Institución Educativa los Olivos Nº 00884 del distrito de Nueva Cajamarca. - Gonza Vicente, Milton (2009)
The investigation(research) named PRINTEO TEXT 11 EXPERIMENTAL PHYSICS 11 ANO THE LEARNING OF THE STUOENTS IN THE AREA OF SCIENCE TECHNOLOGY ANO ENVIRONMENT OF 5t0 OEGREE OF SECONOARY EOUCATION IN THE EOUCATIONAL INSTITUTION THE OLIVE TREES N° 00884 OF THE OISTRICT OF NEW CAJAMARCA, has far aim(lens) demonstrate that the application of the didactic Material Printed Text 11 Experimental Physics ", it (he, she) will influence significantly in the learning of the students of the fifth degree of secondary education, in the area of Science Technology and Environment of Secondary Education, in the Educational lnstitution The Olive trees N ° 00884, of the district of New Cajamarca. On the basis of the theories psicopedagógicas of the learning, theory of the significant learning, theory of the active learning, theory of the cooperative learning and theory of the learning far discovery, there is hipotetizado that the Printed Text "Experimental Physics " will influence significantly in the learning of the students in the area of Science Technology and Environment of 5to degree of Secondary Education in the Educational lnstitution The Olive trees N ° 00884 of the district of New Cajamarca. The sample was constituted by 8S students, of which 29 constituted the experimental group and 56 the group control. To whom 1 they administer a written test (proof) of 24 articles, distributed in: 10 for the capacity of comprehension of information, 10 for the capacity of investigation and experimentation and 04 for the capacity of critical judgment (reason). Tried the information by means of the comparison of averages of the posttest (postproof) of the experimental group and control, with z calculated (12,03) major that z tabulated (1 ,64), allows to establish that the Printed Text " Experimental Physics 11 influences significantly in the learning of the students in the area of Science Technology and Environment of 5to degree of Secondary Education in the Educational lnstitution The Olive trees N° 00884 of the district of New Cajamarca.